KOMITE AUDIT DAN KREDIBILITAS PENGUNGKAPAN CSR: BUKTI DARI PERUSAHAAN PERTANIAN DI BURSA EFEK INDONESIA - Helmaini, Mesi; Azmi, Zul; Aristi, Mentari Dwi (Politeknik Raflesia Press, 2023)
This study aims to examine and analyze the influence of independent audit committees, audit committee financial expertise, frequency of audit committee meetings and audit committee gender in increasing the credibility of CSR disclosure: in agricultural companies on the Indonesia Stock Exchange. While the sample in this study used purposive sampling with a total sample of 41. The type of data used in this research is quantitative data in the form of secondary data with collection techniques using documentation. The data analysis technique uses multiple regression and is tested using the t test. The results of this study indicate that independent audit committees, audit committee financial expertise, frequency of audit committee meetings and audit committee gender in increasing the credibility of CSR disclosure: in agricultural companies on the Indonesia Stock Exchange.